THE INFLUENCE OF PROMOTION AND PRICE TOWARD PURCHASE DECISION OF USED CARS IN THE SHOWROOM MURDIK MOTOR PURWAKARTA REGENCY - Akbar, Rian Prasetia; Asfahani, Rayhan; Zihad, Mochamad; Darmawan, Apriansyah, Nugraha; Hendri, Meriza; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
Used cars have become an option for people in Purwakarta Regency, Indonesia. One of the showrooms that offer used cars is Murdik Motor. Data showed that sales of used cars in this showroom decreased in 2020 and 2021. Sales from 2015 to 2019 increased, while in the years 2020 and 2021, sales decreased. It is supposed to relate to promotion and price. The purposes of this study are to know and analyze promotion, price, and purchase decision of used cars in the Murdik Motor showroom and the influence of promotion toward purchase decision and the influence of price toward purchase decision. Descriptive and verificative methods are used to answer the research question. Data were collected from 36 customers. The questionnaire was used to collect data besides obersvation, interview and literature study. The results showed that promotion is good, price is very good, and the purchase decision is reasonable. Based on the test results of multiple linear regression analysis, it was found that the promotion influences decision to purchase a used car in the Showroom Murdik Motor Purwakarta Regency. Prices also influences purchase decision. The influence of prince toward purchase decision of used cars in Murdik Showroom is higher than promotion.